Literatura caboverdiana : emigração, diáspora e erotismo em contos de Basileia, de Tchalé Figueira - Silva, Jair Lima da (2018)
Nowadays, the archipelago of Cape Verde shows itself as a country endowed with a diverse literature, in which island culture, social conflicts and the diaspora issue are present. Among his writers who seek affirmation in the field of letters is Tchalé Figueira, a Cape Verdean with a great emphasis on expressionist painting and who in recent years has been winning the readers as a short storyteller. The present study aimed to analyze diaspora, eroticism and alter ego of the author in the book Tales of Basel, published in 2011. Based on the results obtained, it can be said that diaspora is present throughout the context of the narrative, with the character Silva revealing his experience with other emigrants as Colombians, Chileans, Turks, Brazilians, Nigerians, among others, who cross, share experiences of communities of expatriate minorities, seeking foreign land to restore life, but not open project return to the country of origin. As for eroticism, this is in the torrid relations between the character and the beautiful women, described as sensual, with burning kisses with whom he maintains moments of love in a climate of intense sexual load and a pleasurable explosion. With regard to the alter ego of the author Tchalé is glimpsed in each line written, in each scene of the plot. He is, therefore, a writer who allows himself to appear in the experience of the character traced by the strength of the memories of the diasporic fate that deeply affected him. Thus, one can conclude that Tales of Basel is a work of autobiographical character, marked by the diasporic experience of the writer and brings the peculiar traits of Tchalé literature: eroticism in high content Keywords: Tales of Basel. Diaspora. Emigration. Eroticism. Alter ego.